Placental Galectins Are Key Players in Regulating the Maternal Adaptive Immune Response - Balogh, Andrea; Toth, Eszter; Romero, Roberto; Parej, Katalin; Csala, Diana; Szenasi, Nikolett L.; Hajdu, Istvan; Juhasz, Kata; Kovacs, Arpad F.; Meiri, Hamutal; Hupuczi, Petronella; Tarca, Adi L.; et al. (Frontiers in Immunology, 2019)
Galectins are potent immunomodulators that regulate maternal immune responses in pregnancy and prevent the rejection of the semi-allogeneic fetus that also occurs in miscarriages. We previously identified a gene cluster on Chromosome 19 that expresses a subfamily of galectins, including galectin-13 (Gal-13) and galectin-14 (Gal-14), which emerged in anthropoid primates. These galectins are expressed only by the placenta and induce the apoptosis of activated T lymphocytes, possibly contributing to a shifted maternal immune balance in pregnancy. The placental expression of Gal-13 and Gal-14 is decreased in preeclampsia, a life-threatening obstetrical syndrome partly attributed to maternal anti-fetal rejection. This study is aimed at revealing the effects of Gal-13 and Gal-14 on T cell functions and comparing the expression of these galectins in placentas from healthy pregnancies and miscarriages. First-trimester placentas were collected from miscarriages and elective termination of pregnancies, tissue microarrays were constructed, and then the expression of Gal-13 and Gal-14 was analyzed by immunohistochemistry and immunoscoring. Recombinant Gal-13 and Gal-14 were expressed and purified, and their effects were investigated on primary peripheral blood T cells. The binding of Gal-13 and Gal-14 to T cells and the effects of these galectins on apoptosis, activation marker (CD25, CD71, CD95, HLA-DR) expression and cytokine (IL-1, IL-6, IL-8, IL-10, IFN) production of T cells were examined by flow cytometry. Gal-13 and Gal-14 are primarily expressed by the syncytiotrophoblast at the maternal-fetal interface in the first trimester, and their placental expression is decreased in miscarriages compared to first trimester controls. Recombinant Gal-13 and Gal-14 bind to T cells in a population- and activation-dependent manner. Gal-13 and Gal-14 induce apoptosis of Th and Tc cell populations, regardless of their activation status. Out of the investigated activation markers, Gal-14 decreases the cell surface expression of CD71, Gal-13 increases the expression of CD25, and both galectins increase the expression of CD95 on T cells. Non-activated T cells produce larger amounts of IL-8 in the presence of Gal-13 or Gal-14. In conclusion, these results show that Gal-13 and Gal-14 already provide an immunoprivileged environment at the maternal-fetal interface during early pregnancy, and their reduced expression is related to miscarriages.